IMPROVING READING COMPREHENSION OF THE EIGHTH-GRADE STUDENTS OF SMP (SLUB) SARASWATI 1 DENPASAR THROUGH KWL - Dede Putra Prawira Adhinatha; I Komang Budiarta; Ni Wayan Krismayani (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
Reading comprehension is the process of acquiring knowledge and comprehending the meaning of printed items. It is a necessary language ability that must be mastered. Initial research revealed that the majority of the eighth-grade students of SMP (SLUB) Saraswati 1 Denpasar struggled with reading comprehension, particularly identifying general and specific information, textual meaning, and textual reference. Moreover, the purpose of the study was to determine whether the reading comprehension of the eighth-grade students of SMP (SLUB) Saraswati 1 Denpasar could be enhanced using KWL (Know Want Learn). To achieve the objective, the researcher performed classroom action research in two cycles. Research instruments, including tests and a questionnaire, were used to obtain the necessary data. Afterwards, the data were examined by comparing pre- and post-test findings. On the basis of the findings, it was evident that the subjects’ mean scores improved significantly between the pre- and post-tests. As supporting data, the questionnaire was also completed at the end of the last cycle; the results indicated good responses to the implementation of KWL. Therefore, it could be concluded that implementing KWL could increase reading comprehension of the eighth-grade students of SMP (SLUB) Saraswati 1 Denpasar.